DISTRIBUTION OF PERTUSSIS CASES ACCORDING TO DPT, HB-HIB4 IMMUNIZATION COVERAGE IN EAST JAVA PROVINCE IN 2022-2023 - Wulan Wijayanti, Esti; Atoillah Isfandiari, Muhammad; Yudi Purnomo, Agoes (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Pertussis is still a health problem in East Java. In 2023 Pertussis cases increased 6 times more than in 2022. DPT-HB-Hib4 immunization coverage in 2023 of 85% is still below the target (>95%). Objective : To analyze the distribution of pertussis cases based on immunization coverage in East Java Province. Research Methods/ Implementation Methods : Descriptive observational study design. Data were collected from the profile of the East Java Provincial Health Office in 2022 and 2023. Descriptive data analysis using epi info (epimap) version 7.0. Results : The number of pertussis cases in 2022 amounted to 33 cases increasing to 165 cases in 2023. DPT-HB-Hib4 immunization coverage in East Java decreased, from 18 districts/cities (47%) in 2022 to 11 districts/cities (29%) in 2023. Of all pertussis cases in 2023, 135 cases (81.35%) occurred in areas with low immunization coverage and 30 (18.65%) cases occurred in areas with targeted immunization coverage. Conclusion/Lesson Learned : The increase in pertussis cases in East Java in 2023 allegedly due to a decrease in DPT-HB-Hib4 coverage. It is recommended to conduct “Imunisasi Kejar”, especially in areas that did not reach target the DPT-HB-Hib4 target.